Microanatomy alteration of gills and kidneys in freshwater mussel (Anodonta woodiana) due to cadmium exposure - FUAD FITRIAWAN; SUTARNO SUTARNO; SUNARTO SUNARTO (Smujo International, 2011)
Abstract. Fitriawan F, Sutarno, Sunarto. 2011. Microanatomy alteration of gills and kidneys in freshwater mussel (Anodonta woodiana) due to cadmium exposure. Nusantara Bioscience 3: 28-35. The purpose of this study was to determine the level of Cd accumulation in the gills and kidneys, to know the changes in microanatomic structure of A. woodiana after the various treatments of heavy metals. Completely randomized design pattern of 5 x 3 as used in this laboratory experiment. The amount of exposure of heavy metals Cd was (0 ppm, 0.5 ppm, 1 ppm, 5 ppm, 10 ppm), while the variation of length of exposure time to Cd were (7 days, 14 days, and 30 days). The parameters of Cd accumulation in the gills and kidney was analyzed by using AAS method, while abnormalities of gills and kidney were detected by microanatomy structure. Data collected were then analyzed using the analysis of variance (ANOVA) and continued with further test the DMRT. The results indicated that there is a significant effect in 475.3 > 0.000 and 60150.3 >0.000 with 5% significance level (P<0.05) of Cd treatment on gill and kidney microanatomy of A. woodiana. The changes in microanatomy structure of those organs are including edema, hyperplasia, fusion of lamella, necrosis, and atrophy.